2011
DOI: 10.1016/j.jpsychires.2011.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combat deployment on risky and self-destructive behavior among active duty military personnel

Abstract: Rabenhorst, Mandy M.; and Milner, Joel S., "Effects of combat deployment on risky and self-destructive behavior among active duty military personnel" (2011 a b s t r a c tAlthough research has documented negative effects of combat deployment on mental health, few studies have examined whether deployment increases risky or self-destructive behavior. The present study addressed this issue. In addition, we examined whether deployment effects on risky behavior varied depending on history of pre-deployment risky b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 51 publications
0
29
0
Order By: Relevance
“…willingness to drive fast) associated with combat exposure. 27 Examining refined indicators of health risk behaviors (e.g., record of pre-deployment risk taking, type of psychiatric diagnosis) 28,29 and timing of mental health diagnoses relative to deployment would strengthen the ability to target preventive interventions.…”
Section: Discussionmentioning
confidence: 99%
“…willingness to drive fast) associated with combat exposure. 27 Examining refined indicators of health risk behaviors (e.g., record of pre-deployment risk taking, type of psychiatric diagnosis) 28,29 and timing of mental health diagnoses relative to deployment would strengthen the ability to target preventive interventions.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear what other factors may influence risk propensity following combat exposure. Likewise, in a recent study, Thomsen et al (2011) found that when surveyed, service members who had deployed reported engaging in more risky behaviors than those who had never deployed.…”
mentioning
confidence: 92%
“…These changes in beliefs and behaviors are not a manifestation of any mental illness but may function as a coping mechanism (Bell et al, 2001). Whereas the Thomsen et al (2011) recent cross-sectional study reported changes in behavior from pre-to post-deployment, a longitudinal study will provide stronger evidence to our understanding of the relationships between deployment and adverse health outcomes.…”
mentioning
confidence: 98%
“…SUD within military veteran populations is associated with a wide range of negative outcomes, including considerable functional impairment (Erbes, Kaler, Schult, Polusny, & Arbisi, 2011), high rates of co-occurring psychiatric disorders (Carter, Capone, & Eaton Short, 2011), and poor treatment outcomes (Ilgen, McKellar, & Tiet, 2005). Importantly, however, a dearth of research has explored involvement in risky behaviors (e.g., risky sexual behavior, deliberate self-harm) among military veterans with SUD, despite evidence of heightened risky behaviors among both civilian SUD patients (Gratz & Tull, 2010b; Tull, Weiss, Adams, & Gratz, 2012; Weiss, Tull, Viana, Anestis, & Gratz, 2012) and military veterans without SUD (Borders, McAndrew, Quigley, & Chandler, 2012; Thomsen, Stander, McWhorter, Rabenhorst, & Milner, 2011). Further, no studies to date have explored factors that may underlie risky behaviors within this at-risk population.…”
mentioning
confidence: 99%